ANALISIS TINGKAT EFISIENSI DAN EFEKTIVITAS UNTUK MENGUKUR KINERJA PENGELOLAAN KEUANGAN MBS DI SDN 2 POHGADING KABUPATEN LOMBOK TIMUR - ERVIVA FARIANTIN1; ELVINA SETIAWATI; ULFIYANI ASDIANSYURI (GANEC SWARA, 2023)
The research aims to analyze and measure  a school performance that has applied school based management (MBS). The study was conducted at SDN 2 Pohgading through descriptive quantitative. The study was conducted through measuring the finance management performance at SDN 2 Pohgading through the measurement of public sector observed from efficiency and effectiveness level. The efficiency measurement is related to estimate purpose meanwhile the effectiveness measurement is related to the target achievement that appropriate with the plan. Data resources gained from: Activity plans and school estimate (RKAS) and realization school estimate report. The results of this study indicates that finance management of school based management performance at SDN 2 Pohgading in 2014-2018 in from of school operational fun aid (BOS) is considered fine. Based on the results of the study through measuring public sector performance indicates that efficiency level reached is 100% in 2014-2018. Based on the table of finance efficiency performance criteria, it is inefficient or equilibrate efficient because it is equal to 100%. However, from the effectiveness level in 2014 it reached 102,43% and in 2016 it reached 100,18%. . Based on the  finance effectiveness performance criteria is categorized very effective. In 2015, 2017 and 2018 the levrl of effectiveness reached 100%. Based on the table of finance effectiveness performance criteria is categorized effective.